Case series: Occlusion using gelatin sponge in modified coil-assisted retrograde transvenous obliteration (Og-CARTO) for the treatment of portal hypertensive varices - Shin Chibana; Hiroyuki Sakakibara; Sota Oguro; Takuma Usuzaki; Hiroki Kamada; Hiromitsu Tannai; Kei Takase (Radiology Case Reports)
We present occlusion using gelatin sponge in modified coil-assisted retrograde transvenous obliteration (Og-CARTO), a novel technique based on CARTO that incorporates gelatin sponge for variceal obliteration. This technique uses 2 microcatheters: 1 for sparse coil embolization in the efferent vein and the other to inject large gelatin sponge particles (5-mm squares) into the varices, facilitating controlled blood flow stagnation prior to sclerosant administration. By eliminating prolonged balloon occlusion, Og-CARTO simplifies the procedure and reduces procedural burden. We successfully applied this technique in three cases with varying variceal anatomies, achieving complete thrombosis without significant complications. Og-CARTO provides a practical, cost-effective alternative when balloon occlusion is challenging and shows potential for broader clinical application.